The Development of a Website For Endeng-Endeng Music in Mandailing Batak Wedding Ceremonies - Irna Yani Siregar; Herlina Jasa Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to develop a German-language website as a cultural learning medium focusing on Endeng-Endeng music in Mandailing Batak wedding ceremonies. The research employs a qualitative descriptive approach using the Richey and Klein development model, which consists of planning, development, and evaluation phases. Data were collected through semi-structured interviews, participant observation, questionnaires, and documentation. The primary informant was an experienced Endeng-Endeng musician with deep knowledge of its cultural values and performance practices. The research was conducted in Tanjung Medan, a region where Mandailing traditions are still actively preserved. The planning phase involved needs analysis and data collection to determine content and design specifications. The development phase focused on creating a user-friendly and informative website by applying instructional design and UI/UX principles. The evaluation phase involved expert validation to assess the quality and effectiveness of the website. The results indicate that the developed website is a relevant and accessible medium for introducing and preserving Endeng-Endeng music, particularly for students and global audiences interested in Indonesian cultural heritage.